Educational Technology - Huang, Ronghuai; Spector, J. Michael; Yang, Junfeng (Springer, 2019)
Educational technology is the study and ethical practice of facilitating learning and improving performance by creating, using, and managing appropriate technological processes and resources. From the perspective of technology used in education, educational technology could be understood as the use of emerging and existing technologies to improve learning experiences in a variety of instructional settings, such as formal learning, informal learning, non-formal learning, lifelong learning, learning on demand, and just-in-time learning. Educational technology approaches have evolved from early uses of audiovisual aids to individual and networked computers, and now have evolved to include various mobile and smart technologies, as well as virtual and augmented realities, avatar-based immersive environments, cloud computing, and wearable and location-aware devices. Various terms have been used along the way to refer to educational technologies, such as learning technologies/environments and instructional technologies/systems. We have embraced a broad interpretation in this book to cover instructional design approaches, learning strategies, and hardware and software. Our view is that anything that consistently can support learning and instruction can be considered an educational technology. Some educational technologies are simple and have existed for many years; others are complex, and new ones are finding their way into educational settings every day. Educational technology focuses on both the technical and pedagogical ways and means of supporting learning and instruction. It is the basis for the success of the e-learning revolution in recent years. Technology-based instruction can surpass traditional classroom-based instruction in quality by providing a wide variety of affordances and capabilities that can promote motivation and result in engaging, efficient, and effective learning.
A Primer for the 21st Century